2021
DOI: 10.3389/fcvm.2021.694365
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Right Ventricular 3D Speckle-Tracking Strain and Ejection Fraction in Patients With HFpEF

Abstract: Background: Right ventricular longitudinal strain of free wall (RV FWLS) assessed by two-dimensional speckle-tracking echocardiography (2D-STE) is recognized as an independent predictor of poor prognosis in patients with heart failure with preserved ejection fraction (HFpEF). However, the prognostic implications of three-dimensional STE (3D-STE) parameters in patients with HFpEF have not been well-established. The purpose of our study was to determine whether 3D-STE parameters were the more powerful predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…A number of factors could affect the prognosis of HFpEF (37)(38)(39)(40)(41). LV diastolic dysfunction plays a central role in the pathophysiology of HFpEF, defined as an impairment in relaxation or an increase in stiffness.…”
Section: Comorbidities and Prognostic Factors In Hfpefmentioning
confidence: 99%
“…A number of factors could affect the prognosis of HFpEF (37)(38)(39)(40)(41). LV diastolic dysfunction plays a central role in the pathophysiology of HFpEF, defined as an impairment in relaxation or an increase in stiffness.…”
Section: Comorbidities and Prognostic Factors In Hfpefmentioning
confidence: 99%
“…Most studies on RV GLS focus on patients with HFrEF. In a recent study by Meng et al, 81 patients with HFpEF were followed up with speckle-tracking echocardiography [22]. RV GLS was an independent predictor of death or hospitalization due to CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, by Shanbhag et al, that followed a community-based sample of older adults for a median of 5.8 years showed that patients with NICM had a worse prognosis than those with ICM ( 6 ). Likewise, Meng et al also demonstrated that patients with HF with poor clinical outcomes displayed impaired 3D-RVFWLS and RVEF compared to those without clinical events ( 27 ). Our findings provide direct evidence to support the aforementioned results.…”
Section: Discussionmentioning
confidence: 99%